FAKTOR-FAKTOR YANG MENJADI PENGHAMBAT DALAM PEMBERIAN REMISI TERHADAP NARAPIDANA (STUDI KASUS DI LEMBAGA PEMASYARAKATAN KLAS IIA DENPASAR) - Satrya Budhi Prabawa, I Kadek; Mertha, I Ketut; Suardana, I Wayan (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 02, Februari 2013, 2013)
Remissions for the criminal is an order of regulations as excitement, to make the criminal feel disposed for go through a period of development for change behavior fit for purpose of penal system. But in the implementation which involved many institutions and agencies outside from penitentiary were not accompanied with the strict rules. Therefore caused some difficulties in barriers precisely in giving remissions for the criminal
Keywords: Remissions, Criminal, Penal System, Penitientiary.